Effectiveness of dermal cleaning interventions for reducing firefighters' exposures to PAHs and genotoxins. Issue 2 (1st February 2023) - Keir, Jennifer L. A.; Kirkham, Tracy L.; Aranda-Rodriguez, Rocio; White, Paul A.; Blais, Jules M.
Abstract: Firefighters are exposed to carcinogenic and mutagenic combustion emissions, including polycyclic aromatic hydrocarbons (PAHs). Fire service and firefighter cancer advocacy groups recommend skin cleaning using wipes or washing with detergent and water after exposure to smoke, although these strategies have not been proven to reduce exposures to harmful combustion products such as PAHs. This study assessed dermal decontamination methods to reduce PAH exposures by firefighters participating in live fire training scenarios. Study participants ( n = 88) were randomly assigned to an intervention group (i.e., two types of commercial skin wipes, detergent and water, or a control group who did not use any skin decontamination). PAHs were measured in personal air (during the fire) and dermal wipe samples (before and after fire suppression and after dermal decontamination). PAH metabolites and mutagenicity were measured in urine samples before and after fire suppression. Airborne PAH concentrations during the fire ranged between 200 and 3, 970 μg/m 3 (mean = 759 μg/m 3, SD = 685 μg/m 3 ). Firefighters had higher total PAHs and high-molecular-weight PAHs on their skin after the fire compared to before (1.3- and 2.2-fold, respectively, p < 0.01). Urinary PAH metabolites increased significantly following exposure to the training fires by 1.7 to 2.2-fold (depending on the metabolite, p < 0.001). Urinary mutagenicity did not differ significantly between pre- and post-fire for any of the decontamination methods. Detergent and water was the only intervention that removed a significant amount of total PAHs from the skin (0.72 ng/cm 2 preintervention vs. 0.38 ng/cm 2 postintervention, p < 0.01). However, fold changes in urinary PAH metabolites (i.e., pre- vs. post-exposure levels) did not differ among any of the dermal decontamination methods or the control group. These data suggest that despite on-site attempts to remove PAHs from firefighters' skin, the examined interventions did not reduce the internal dose of PAHs. Future work should investigate preventing initial exposure using other interventions, such as improved personal protective equipment.